Role Stress sebagai Motivator Bagi Auditor: Analisis Teoritis Atas Dasar Teori-teori Motivasi - Anggraini, Francisca Reni Retno (Bina Nusantara University, 2008)
The purpose of this paper explains the positive side of role stress which has long been regarded as the factor causing performance decrease and ultimately initiates job dissatisfaction. There are many cause factors (antecedent) of role stress such as boundary-spanning activities, ethical climate in organization, mentoring, and organization-professional conflict, which has been proven empirically affecting role stress. Role stress arising in the job relation between manager-subordinate or leader-his or her member is a dynamic process in organization. Role stress becomes potential resource for organization if manager or leader is able to manage it well, so he or she can change it from hygiene factor to motivator. This article tries to correlate role stress phenomenon in public accountant firms with motivation theories to give alternatives in resolving problems in the role stress. Role stress can become a motivator for partners or senior auditors to be able to suit job characteristics and reward/punishment award mechanism with personal characteristics of auditors, reduce boundary spanning activities and environment uncertainty perception, increase understanding among all individuals in the public accountant firm regarding demand, values, and norms of the said public accountant firm, and ultimately establish specific and attainable goals. This article aims to be a contribution for management (partners and senior auditors) in motivating auditors to increase their performance and for researchers to inspire empiric research related to role stress as a motivator to increase performance.